(untitled) (International Journal of Engineering and Computer Science, 2013)
Unlike traditional routing schemes that route all traffic along the same path, multipath routing method split the traffic among several paths in order to ease congestion. It has been recognized by many that multipath routing can be fundamentally more efficient than the traditional approach of routing along single paths. Yet, in contrast to the single path routing approach, many research in the context of multipath routing focused on heuristic methods. We demonstrate the significant advantage of optimal (or near optimal) solutions. Hence, we investigate multipath routing. A wireless sensor network is a large collection of sensor nodes with limited power supply and constrained computational capability. Because of the restricted communication range and high density of sensor nodes, packet forwarding in sensor networks is usually performed through multi-hop data transmission. We present a comprehensive taxonomy on the existing multipath routing protocol called network coding based multipath routing, which is especially designed for wireless sensor network and provide an enhancement to that algorithm that gives better packet delivery, packet delivery delay, less packet loss probability and network life time.